2012
DOI: 10.1039/c2cc33266c
|View full text |Cite
|
Sign up to set email alerts
|

Sensing using localised surface plasmon resonance sensors

Abstract: The bright colours of noble metal particles have attracted considerable interest since historical times, where they were used as decorative pigments in stained glass windows. More recently, the tuneable optical properties of metal nanoparticles and their addressability via spectroscopic techniques have brought them back into the forefront of fundamental and applied research fields. Much of the recent attention concerning metal nanoparticles such as gold and silver has been their use as small-volume, ultra-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
209
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(211 citation statements)
references
References 103 publications
1
209
0
1
Order By: Relevance
“…Among the nanoparticles currently considered for cancer, gold nanostructures are particularly well-suited. [5][6][7][8][9][10][11] The localized surface plasmon resonance (LSPR) of gold nanoparticles 12 endows them with the capability to strongly absorb light at a specific wavelength, which can be controlled and tuned through synthetic means. Photo-excitation of gold nanostructures at their LSPR band can efficiently convert photon energy into heat and can be used for the photothermal ablation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nanoparticles currently considered for cancer, gold nanostructures are particularly well-suited. [5][6][7][8][9][10][11] The localized surface plasmon resonance (LSPR) of gold nanoparticles 12 endows them with the capability to strongly absorb light at a specific wavelength, which can be controlled and tuned through synthetic means. Photo-excitation of gold nanostructures at their LSPR band can efficiently convert photon energy into heat and can be used for the photothermal ablation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonics emerged mostly in the 1990s as an extremely rich new domain in optics, exciting due to its many applications ranging from simply down-scaling the conduction of light in subwavelength devices [1], to designing nanosources of light [2], new single-molecules biosensors [3], developing innovative treatment in cancer therapy [4], efficient and cheap solar cells [5], or designing an entirely new type of metamaterials, where "atoms" are artificially built as complex optical nanostructures allowing for the manipulating of light at will in ways not found in nature [6]. Specifically, surface plasmons are optical modes bound to the interface between a dielectric and a metal nano-object, which originate from the resonant coupling between a surface-charge oscillation and the electromagnetic field that it scatters.…”
Section: Introduction and Basicsmentioning
confidence: 99%
“…92,93 Due to their small size, large surface area to volume ratio, stability over high temperature and translocation into the cells, inorganic nanoparticles are considered as a viable alternative for carrying a large amount of antibiotics and the efficacy of metallic NPs conjugated with antibiotics has thus been the subject of intense investigations. These studies showed that gold nanostructures 94,95 used in combination with antibiotics exhibit enhanced bactericidal activity on a range of Gram-positive and Gramnegative bacteria and higher stability over an extended storage compared to the free antibiotics (Table 6).…”
Section: Gold and Silver Nanostructuresmentioning
confidence: 99%